2002
DOI: 10.1109/tbme.2002.803588
|View full text |Cite
|
Sign up to set email alerts
|

A versatile microwave plethysmograph for the monitoring of physiological parameters

Abstract: A simple microwave technique for in vivo monitoring of human pulmonary and cardiac activity is here presented. The technique is based on detecting the changes in the modulation envelope of amplitude modulated waves passing through the human body. A simplified human chest model was developed, proving an unambiguous correlation between heart blood filling and microwave transmission through the chest. A prototype system for transmittance measurement was realized at the 868.5-MHz operating frequency, demonstrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In this case, the descriptors of the images were computed using HOG with the parameters, i.e., number of cells per block, number of pixels per cell, number of bins etc., that the paper [8] mentioned were the best for pedestrian detection. From this experimentation we found that the linear SVM was the one that resulted in the lowest error rate in human activity recognition.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In this case, the descriptors of the images were computed using HOG with the parameters, i.e., number of cells per block, number of pixels per cell, number of bins etc., that the paper [8] mentioned were the best for pedestrian detection. From this experimentation we found that the linear SVM was the one that resulted in the lowest error rate in human activity recognition.…”
Section: Resultsmentioning
confidence: 97%
“…Each descriptor with its corresponding label represented a learning instance. For obtaining the descriptor, we implemented in Open CV-C++ the HOG [8] and the PHOG [9]. The design parameters that were taken in HOG were the number of bins that the histogram has, the number of pixels per cell, and the number of cells per block.…”
Section: Offline Training Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The biofeedback has been used in the rehabilitation field, mainly in patients with hemiparetic condition due to a stroke or in spinal cord injury [3,4] others apply biofeedback to train elderly people and prevent falls [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known from communication theory that using coded waveforms along with coherent demodulation leads to the highest power efficiency [3]. The implant uses a crystal controlled local oscillator, combined with a digital delay locked loop (DDLL) to maintain continuous timing accuracy relative to the MCU.…”
Section: Present Statusmentioning
confidence: 99%